(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper examines the combined effects of globalization and governance on economic growth in selected Asian economies using annual panel data from 2002 to 2019. The empirical model is an integration of main macroeconomic variables, gross domestic product, labor force participation, gross fixed capital formation, trade openness, government spending, and consumption in the hands of the private, but a composite governance index derived using the World Governance Indicators. The panel unit root tests (LLC and IPS) indicate a combination of both I(0) and I(1) variables and no I(2) series, which explains the use of a panel autoregressive distributed lag (ARDL) model to differentiate between long-run and short-run dynamics. The long-run findings indicate that labor force participation, capital formation, government spending, and consumption have positive and statistically significant effects on economic growth. Trade openness, however, has a small but negative long-run relationship. The value of the error-correction term is negative and substantial, indicating the presence of a stable long-run equilibrium among the variables. The variations in capital formation, trade openness, and government spending in the short-term favour higher growth, suggesting that openness can be growth-promoting in the adjustment process, even though it has a negative long-run impact. In general, the evidence indicates the need to enhance governance quality, reinforce productive investment, and structure complementary policies so that globalization and open trade yield long-term economic growth in Asian economies.​